Leptospirosis in Malaysia: current status, insights, and future prospects - Noraini Philip; Kamruddin Ahmed (BioMed Central Ltd., 2023)
Among zoonotic infections, leptospirosis has a worldwide distribution and high prevalence in tropical regions. It has a broad clinical presentation from mild to severe, life-threatening infection. Leptospires, the etiological agent of leptospirosis, are found in varied ecological niches and animal species, providing a signifcant source of human infection. This review aims to provide the current status of leptospirosis in Malaysia and the direction for future studies. The literature search for this review was performed using PubMed, Web of Sciences, and Google Scholar databases. The incidence of leptospirosis in Malaysia from 2004 to 2020 varied; however, a large number of cases occurred during foods. Leptospira has been isolated from wild and domestic animals as well as from the environment; among them, several novel species have been identifed. In Malaysia, leptospirosis infection and death were mostly associated with recreational and non-recreational water activities. Despite the endemicity of leptospirosis, the public’s knowledge, attitude, and practice level are relatively low in this country. More studies are needed in Malaysia to explore the extent of leptospirosis in diferent settings and locations.